2021
DOI: 10.1080/10942912.2021.1953071
|View full text |Cite
|
Sign up to set email alerts
|

Ripening and ethylene production affected by 1-MCP in different parts of kiwifruit during postharvest storage

Abstract: Ethylene plays an important role in kiwifruit ripening. However, it is unclear whether there are differences in ethylene production in different parts of kiwifruit during postharvest ripening. Kiwifruit were treated with 0.5 μL L −1 1-MCP for 12 h at 20°C and stored at 20 ± 1°C. The results showed the firmness, soluble sugar, total soluble solids (TSS), and AcACS1 and AcETR2 gene expressions were the highest in the core, and starch, AcACO2, and AcACO3 gene expressions were the highest in the seedless pulp at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As shown in Figure 7 , the production of endogenous ethylene is significantly negatively correlated with firmness but is positively correlated with MDA content. These results indicate that ETH may accelerate the softening and ripening by regulating the production of endogenous ethylene in postharvest mango fruit ( 47 ). Second, previous reports have shown that chlorophyll was the main pigment masking the contribution of carotenoids and anthocyanins, leading to the green color of fruit peel ( 18 ).…”
Section: Discussionmentioning
confidence: 82%
“…As shown in Figure 7 , the production of endogenous ethylene is significantly negatively correlated with firmness but is positively correlated with MDA content. These results indicate that ETH may accelerate the softening and ripening by regulating the production of endogenous ethylene in postharvest mango fruit ( 47 ). Second, previous reports have shown that chlorophyll was the main pigment masking the contribution of carotenoids and anthocyanins, leading to the green color of fruit peel ( 18 ).…”
Section: Discussionmentioning
confidence: 82%
“…These obtained performance criteria confirm the appropriate potential of the e‐nose system for nondestructive monitoring of the kiwifruit postharvest ripening. According to literature, a characteristic event during the ripening of kiwifruit, besides its softening, acidity reduction, and starch‐to‐sugar conversion, is the aroma development (Asiche et al, 2017 ; Liu et al, 2021 ). The concentration of ripeness‐dependent VOCs is positively correlated with SSC, and negatively correlated with flesh firmness (Sanchez et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%